2006
DOI: 10.1111/j.1556-4029.2006.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination Using Nonmetric Characteristics of the Mandible in Koreans*

Abstract: The mandible is the largest and hardest facial bone and retains its shape better than other bones in the forensic and physical anthropologic field. The mandible can be used to distinguish among ethnic groups and between sexes. We examined the morphological characteristics of the mandibles of 102 Koreans of either sex. Of 13 nonmetric items of the mandible, the characteristic that best allowed the sexes to be distinguished was the contour of the lower border of the mandible: rocker-shaped mandibles predominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 9 publications
2
77
0
7
Order By: Relevance
“…This is important and it reinforces the value of the dimorphism morphologic strains. In this respect, Suazo et al (2008 a,b,c) reported good levels of accuracy of the qualitative classic strains of sexual dimorphism in a sample comparable to this study, a situation also described for other populations (Rogers, 2005;Haralabakis et al, 2006;Hu et al, 2006).…”
Section: Discussionsupporting
confidence: 85%
“…This is important and it reinforces the value of the dimorphism morphologic strains. In this respect, Suazo et al (2008 a,b,c) reported good levels of accuracy of the qualitative classic strains of sexual dimorphism in a sample comparable to this study, a situation also described for other populations (Rogers, 2005;Haralabakis et al, 2006;Hu et al, 2006).…”
Section: Discussionsupporting
confidence: 85%
“…Among these factors are sex hormones, such as, estrogen and progesterone that can influence in the growth rate and developmental stages of male and female mandibles. Since females reach puberty earlier than males, development of their mandible and skull appear to either stop or slow down earlier than that in maturing males, thus contributing to the development of craniofacial morphological differences between sexes (Hu et al, 2006;Ongkana & Sudwan). A further controlling factor is the muscular tension, which is considered an inductive factor of bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Mandible is the strongest bone and persists in a well preserved state for a long period. [4,5] Hence, the morphological features of the mandible are commonly used by forensic specialists in determining sex. Sex determination from skeletal remains is an important aspect of the osteologic analysis of a given population.…”
Section: Introductionmentioning
confidence: 99%